Monoclonal antibodies that recognize symbiotic bacteria and hemocytes in the deep-sea vesicomyid clam Phreagena okutanii - Nagai, Yukiko; Kusaka, Chiho; Ohishi, Kazue; Maruyama, Tadashi; Nakazawa, Masatoshi; Nakamura, Yoshimitsu; Yoshida, Takao (JAMSTEC REPORT OF RESEARCH AND DEVELOPMENT, 2018)
Vesicomyid clams, including the genus Phreagena, are dominant members of various deep-sea chemosynthesis-based animal communities. They harbor symbiotic sulfur-oxidizing bacteria in the epithelial cells of their gill tissue, and the bacteria are transmitted to the next generations via eggs. We created a monoclonal antibody (mAb) library against the gill of P. okutanii and observed mAb CokG-D1D3 to react to the symbiotic bacteria and three mAbs (CokG-Y1F7, CokG-J10D2, and CokG-J3G4) to bind to hemocytes of P. okutanii. The signals of mAb CokG-D1D3 were localized in the epithelial gill cells called bacteriocytes. We also observed a small number of clear signals of the antibody in the epithelial follicular cells of the ovary. The signals of mAb CokG-D1D3 almost exactly overlapped those of the anti-E. coli GroEL polyclonal antibody, while, in the gill, the signal areas of the latter seemed to be slightly wider than those of the former. Among the three mAbs against the hemocytes, mAbs CokG-Y1F7 and CokG-J10D2 reacted to a large fraction of the hemocyte populations, but mAb CokG-J3G4 reacted to a smaller fraction. mAb CokG-Y1F7 was observed to bind to the hemocytes distributed widely in the interstitial spaces of various tissues. These monoclonal antibodies are expected to be useful for studying the interactions between symbiotic bacteria and host cells and the distribution and functions of hemocytes in deep-sea vesicomyid clams.